STUDY OF VIBRATION COMBUSTION ENGINES VIBRO-ACOUSTIC TECHNIQUE - , Д. С. (Municipal economy of cities (Technical science), 2013)
The dynamics of reducing the technical characteristics of internal combustion engines based on subjective conclusions , the study of such indirect characteristics as the composition of the exhaust gas flow rate of fuel and lubricants . It is proposed to carry out fault detection state of its parts to change the amplitude and frequency characteristics of vibration and acoustic parameters , ie using passive vibration and acoustic methods. The methods of diagnosis such a crucial task in the operation of the engine.